Co-transfer of gfp, CHS and hptII genes into Oncidium Sharry Baby PLB using the biolistic gun - Ng, Chea Yee; Abdullah, Janna Ong; Mahmood, Maziah; Basiron, Nazir (Academic Journals, 2008)
This study was aimed at assessing the biolistic method of co-transforming non-linked genes on separate gene cassettes into Oncidium Sharry Baby’s protocorm-like-body (PLB). An expression vector containing a synthetic green fluorescence protein (sgfp) gene driven by the Cauliflower Mosaic Virus (CaMV) 35S promoter and another vector containing the antisense chalcone synthase (CHS) and hygromycin resistant (hpt II) genes, were successfully co-bombarded into Oncidium Sharry Baby PLB. Six critical parameters (PLB size, time course of gfp transient expression in PLB, DNA concentration,PLB age, presence of spermidine and CaCl2 in the DNA-microcarrier precipitation, and duration of PLB on fresh medium prior bombardment) were optimized based on transient gfp expression. One month after bombardment, the PLB were subjected to 5 mg/ml hygromycin selection for 8 months. A total of 137 regenerated putative transformants were randomly selected and verified by polymerase chain reaction (PCR) analysis. The results indicated the presence of the transgenes gfp, hptII and antisense CHS in 28, 61, and 11% of the selected putative transformants,respectively.